As inscrições corporais nos diagramas de forças de Deleuze e Guattari - Lima, Luciene Marques de (2018)
This study aimed to know the force vectors of each power diagram to discuss the body inscriptions. The specific objectives were to identify the power diagrams through Deleuze and Guattari's Universal History; analyze the body inscriptions of each diagram; and examine vignettes / narratives of concrete cases as well as legislation and medical practices that express the body inscriptions of the disciplinary diagram and the control and axiomatic of capital. Through research of theoretical he knew the body inscriptions in the different historical formations, adopted the concepts of diagrams elaborated based on the works of Foucault, Deleuze and Guattari using the cartography for the bibliographical revision. We discussed fragments of Brazilian legislation concerning medical and health activity, of the Federal Council of Medicine, the Brazilian Society of Plastic Surgery and of the Brazilian Society of Bariatric and Metabolic Surgery that regulate the medical activity in the areas of plastic surgery and bariatric surgery - gastroplasty. We also discussed three concrete cases extracted from the media to elucidate the body of the capital axiomatics and the body inscriptions of the control diagram, which addressed the adaptations of physicians and patients to capital axiomatics, bariatric surgeries, and silicone implants. Primitive body inscriptions are the marks on the skin that guarantee communal life. The corporal inscriptions of sovereignty are the punishments and tortures imposed on the bodies. The corporal inscriptions of the discipline are the normalization and normalization of the bodies. The body's inscriptions of control are given through the axiomatic of capital that models bodies in the business logic of hypertrophy and continuous growth. The vignettes exemplified the bodily inscriptions of control and the tensions between the codes and the axiomatic of capital.